The Effect of BAP Concentration on In-Vitro Mutant Taro Regeneration - N. Nasaruddin; Feranita Haring; Nuriyah Magfiratul Fara Ramadhani; Salsabila Alisyah; M. Mukminati; A.Chamsitasari Zulfikarahmi A. Jamil; Shelfina Indrayanti (Agrotech Journal, 2022)
Plant regeneration through invitro culture is strongly influenced by the use of growth regulators. BAP is a class of cytokinins that affect cell division which is very well used to stimulate plant growth. The aim of the study was to determine the effect of BAP concentration on the regeneration of various in vitro mutant taro. The study was carried out at the Plant Tissue Culture Laboratory,  Faculty of Agriculture, Hasanuddin University, Makassar. The method used was factorial completely randomized design with 2 factors as the environmental design. The first factor was the BAP concentrations of 0.0 mg/L, 1.0 mg/L, 1.5 mg/L, 2.0 mg/L and 2.5 mg/L. The second factor was mutant plants consisting of control plants (diploid), mutant 1 (Putative-Tetraploid), mutant 2 (Mixoploid), mutant 3 (Mixoploid), and mutant 4 (Putative-Tetraploid). The results showed that the best regeneration was obtained by BAP concentration of 0 mg/L with control plants on the parameters of root length (2.41 cm), number of roots (11.66 pieces) and plantlet formation rate (13 days). The BAP concentration of 1 mg/L was shown by mutant plant 1 on the parameters of the number of shoots (26 pieces) and number of leaves (16 pieces). BAP concentration of 0 mg/L in mutant 4 had a shoot height of 1.83 cm. The results of ploidy flow cytometry analysis of mutant plants with Putative-Tetraploid parental traits after regeneration resulted in detectable diploid chromosomes that were different from the parent types in all BAP concentration treatments